Evaluation of regional climate models and future wave characteristics in an enclosed sea: A case study of the Black Sea - Islek, Fulya; Yuksel, Yalcin; Sahin, Cihan (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
The main objective of this study is to evaluate a possible climate change impact on wave climate in an enclosed sea (Black Sea) until the end of the 21st century. To achieve the goal, the wave data are generated from a third-generation wave model forced with the widely used reanalysis data (Climate Forecast System Reanalysis), and the hindcast wind fields simulated by a Regional Climate Model, namely Rossby Centre regional atmospheric model (version RCA4). The pattern of change in the wave climate is discussed by comparing the historical (1970-2005) with the future for periods 2021-2060 and 2061-2100 under two climate scenarios. The projected changes in the mean wave characteristics are characterized by an increase in the near future for both RCP scenarios that is more prominent under RCP8.5 scenario in the eastern basin. The middle future under RCP8.5 scenario suggests more significant changes in annual mean values than those obtained under RCP4.5 scenario. In the context of climate change, the possible effects are more prominent on extreme wave heights. For example, the increases in the wave heights for the 100-year return period reach the value of 5% and 25% in the western and eastern Black Sea, respectively.
Keywords: Black sea; Wave climate; Climate change; Projections; Future trends; EURO-CORDEX; PROJECTED CHANGES; ENERGY-RESOURCES; WIND; VARIABILITY; PACIFIC; BASIN; POWER; CURL; END; Engineering; Oceanography